Teacher’s Vision and Mission in the Affective Domain: A Takhrij Analysis of the Hadith "Innama Bu’istu Mu’alliman” - Nur, Tya Shofarina M.; Sumarna, Elan; Putra, Moch. Ardia; Kamah, Husna (Jurnal al-Thullab, 2025)
Modern education tends to prioritize the cognitive domain, often neglecting the affective domain, which plays a crucial role in moral and character development—especially in religious education. This study aims to examine the vision and mission of teachers from the perspective of hadith tarbawi, focusing on the role of educators as exemplified in Islamic teachings. The research analyzes the hadith "Innama bu’istu mu’alliman" (Indeed, I was only sent as a teacher), which reflects the prophetic mission of Prophet Muhammad as a moral guide and educator. A qualitative approach is employed through literature study and takhrij al-hadith. Primary sources include classical hadith books such as Sunan Ibn Majah, Sunan ad-Darimi, Musnad Abu Daud al-Tayalisi, Mishkat al-Masabih, and Al-Madkhal ila Sunan al-Kubra. The findings reveal that although the analyzed hadith is categorized as da'if in its sanad, it attains the status of hasan lighairihi due to corroborating authentic narrations regarding moral perfection. This study concludes that the hadith serves as a pedagogical foundation for teachers to prioritize their role as moral inspirators, ensuring a balance between intellectual intelligence and character building. The study is limited to the analysis of five main hadith sources. Future research is recommended to expand the scope by including a broader range of hadith texts and exploring additional educational hadiths more comprehensively.